DRESS Syndrome- A Rare Condition - Hossain, Homayra Tahseen; Islam, Quazi Tarikul; Reza, Ishrat Binte; Chowdhury, Tasmina; Mazumder, Md Maksudul; Ahasan, HAM Nazmul (Bangladesh Journal of Medicine, 2018)
DRESS syndrome (Drug reaction with Eosinophilia and Systemic Symptoms) is a rare but potentially life-threatening drug hypersensitivity reaction characterized by fever, exfoliative dermatitis and maculopapular rash, lymphadenopathy, eosinophilia, leucocytosis, and involvement of internal organs as liver, lung, heart, and kidney. The disorder starts within 2–8 weeks after taking an offending drug. Long latency between drug treatment and onset of symptoms along with variability of presentation make the diagnosis quite difficult. Here, we are presenting a case report of 58 year old male presented with short history of high grade fever with extensive skin rash. Investigations revealed leucocytosis with gross eosinophilia. He gave history of taking carbamazepine for more than last 3 months prescribed by his neurologist. According to the RegiSCAR scoring system, our case could be classified as definite DRESS syndrome. After withdrawal of the offending drug carbamazepine and starting high dose of systemic corticosteroid, he improved dramatically. As this syndrome is quite uncommon, so we are reporting this case. Bangladesh J Medicine Jul 2018; 29(2) : 91-93